Just get on the pill : the uneven burden of reproductive politics - Littlejohn, Krystale E., 1985- (Reproductive justice, 2021)
"The average woman concerned about pregnancy spends approximately thirty years trying to prevent conception. She largely does so alone using prescription birth control, a phenomenon often taken for granted as natural and beneficial in the United States. In Just Get on the Pill, Littlejohn draws on interviews to show how young women come to take responsibility for prescription birth control as the "woman's method" and relinquish control of external condoms as the "man's method." She uncovers how gendered compulsory birth control-in which women are held accountable for preventing and resolving pregnancies in gender-constrained ways-encroaches on women's reproductive autonomy and erodes their ability to protect themselves from disease. In tracing the gendered politics of pregnancy prevention, Littlejohn argues that the gender division of labor in birth control is not natural. It is unjust"--